The terahertz dynamics of simplest fluids probed by inelastic X-ray scattering. Issue 3 (3rd July 2017) - Cunsolo, Alessandro
Abstract: More than two decades of inelastic X-ray scattering (IXS) studies on noble gases and alkali metals are reviewed to illustrate the advances they prompted in our understanding of the terahertz dynamics of simplest systems. The various literature results outline a remarkably coherent picture of common and distinctive behaviours of liquids and their crystalline counterparts. Furthermore, they draw a consistent and comprehensive picture of the evolution of collective modes at the crossover between the hydrodynamic and the single particle regime, their coupling with fast (sub-ps) relaxation processes and their gradual disappearance upon approaching microscopic scales. The gradual transition of the spectrum towards the single particle limit along with its coupling with collisional relaxations will be discussed in some detail. Finally, less understood emerging topics will be discussed as the occurrence of polyamorphic crossovers, the onset of non-hydrodynamic modes and quantum effects on the spectrum, as well as recent IXS results challenging our vision of the supercritical phase as an intrinsically homogeneous thermodynamic domain.